Diagnostic and management dilemma in a case of a huge broad ligament fibroid with retroviral disease - Anand, Ashok R.; Gohil, Dhruv Pravin; Angu, Gamli (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Extrauterine sites of fibroids are known to occur but are extremely rare. Because of its rare occurrence it poses a diagnostic dilemma and management. This is one such case report. A 44 year old retroviral disease positive patient on therapy presented with distension, pain in abdomen and weight loss. Clinical findings and CT scan were consistent with diagnosis of ovarian neoplasm. On exploratory laparotomy a huge broad ligament fibroid was found. Mass removal with total abdominal hysterectomy with bilateral salpingoopherectomy with appendicectomy was done. Post operatively, due to bradycardia and hypotension, patient was re explored and retroperitoneal clot evacuation with bilateral internal iliac ligation was done. Extra-uterine fibroids are uncommon. In this case the examination findings and CT scan findings were consistent with diagnosis of an ovarian neoplasm. Possibility of a giant fibroid with cystic degeneration was distant. Complete haemostasis doesnot always gurantee post-operative haemorrhage. Hence putting a drain in abdomen and observation of vitals is important. Sometimes we believe that a prophylactic internal iliac ligation in cases of huge fibroids may avoid such complications.